Akuntabilitas Pengelolaan Keuangan Daerah dan Tingkat Kepercayaan Publik pada Organisasi Perangkat Daerah di Kota Semarang - Fuad, Khoirul; Yulia Baharani, Rizka (E-Jurnal Akuntansi; Vol 31 No 4 (2021), 2021)
Strategic issues related to regional autonomy are still very important to be studied in depth. The existence of funds that revolve from the central government to the greater area demands transparent accountability both to the central government and stakeholders so that the level of trust that arises is getting better. This study used a quantitative method by distributing questionnaires to the Regional Organization (OPD) in Semarang, Indonesia with an accidental sampling technique to those who are directly related to regional financial management. The results of this study indicate that regional financial management accountability has a positive and significant effect on public stakeholder trust. Therefore, disclosure of financial information and financial accountability from local governments will have a good impact in the future and the behavior of stake holders on local governments will also be better.  Keywords: Accountability; Public Trust; Local Government.